Residuos orgánicos generados en el oriente antioqueño como fuente potencial para la producción de biogás (2021)
Due to its agricultural vocation, Eastern Antioquia has a high generation of organic waste, however, its use is low, only a small percentage is used for fertilizing crops and the rest is taken to landfills or disposed of in the open air causing an alteration of the physicochemical characteristics of the soil and water bodies. Although at present, Eastern Antioquia has programs for the use of organic waste, they are not able to fully manage them. Anaerobic digestion is a process by which organic matter decomposes, resulting at the end of its process biogas which can be used for the generation of heat, energy or both and a digestate that can be used as fertilizer for crops. This type of technology allows managing organic waste and reduces the generation of GHG. Taking into account the potential for the generation of organic waste in Eastern Antioquia, the capacity to generate biogas from agricultural and livestock waste was evaluated. The amount of waste generated by municipalities was estimated indirectly through the hectares cultivated by type of crop and number of animals per municipality. The biogas potential calculation was made theoretically for 16 anaerobic codigestion mixtures, in four areas of the Eastern. Finally, four potential sites were suggested for the location of the biogas plants, defined by the weighted generation centroids method. Eastern Antioquia has a potential generation of 2,674,697 tons of organic waste (livestock and agricultural), with a biogas generation potential of 93,274,280 m3 / year, enough biogas to supply the needs of 45,754,271m3. The four ideal places for the location of biogas plants are in the municipalities of El Carmen de Viboral, Algeria, San Luis and San Rafael